2008
DOI: 10.1002/jbm.a.32000
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface roughness, porosity, and a resorbable calcium phosphate coating on osseointegration of titanium in a minipig model

Abstract: The aim of this study was to compare the osseointegration of four different implant surfaces in the Göttingen minipig femur model. They were prepared by glasspearlblasting (A), sandblasting (B) and titaniumplasma spraying (C and D). Surface D received additionally an electrochemically deposited layer of a resorbable calcium phosphate (CaP) layer, made mainly of brushite. Sample size was n = 20 per group. Implants were placed in the intertrochanteric and intercondylar sites of both femora. After 12 weeks, impla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 53 publications
0
53
0
4
Order By: Relevance
“…To summarize the available information on the biomedical and biomechanical properties of implants coated by CaPO 4 , one can claim the following. If compared to uncoated controls, deposited CaPO 4 were found to induce bone-to-implant contacts [574,818,819,[879][880][881][882][883][884][885][886][887][888][889][890], improve initial stability [891], implant fixation [763,[892][893][894][895][896] and nanomechanical…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…To summarize the available information on the biomedical and biomechanical properties of implants coated by CaPO 4 , one can claim the following. If compared to uncoated controls, deposited CaPO 4 were found to induce bone-to-implant contacts [574,818,819,[879][880][881][882][883][884][885][886][887][888][889][890], improve initial stability [891], implant fixation [763,[892][893][894][895][896] and nanomechanical…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Since then, plentiful reports have been published about the biomedical advantages of such coated implants. To summarize the available information on the biomedical and biomechanical properties of implants coated by calcium orthophosphates, one can claim the following: If compared to uncoated implants, the presence of calcium orthophosphate deposits were found to induce bone contacts to the implants (Dhert et al 1992, 1993; Thomas et al 1989; Jansen et al 1991; Gottlander et al 1997b; Hulshoff and Jansen 1997; Hayakawa et al 2000; Mohammadi et al 2004; Park et al 2005; Siebers et al 2007; Kuroda et al 2007; Chae et al 2008; Schwarz et al 2009; Junker et al 2010; Suzuki et al 2010); improve implant fixation (Yang et al 1997; Søballe et al 1993; Daugaard et al 2010); show higher torque values (Park et al 2005; Junker et al 2010; Granato et al 2009) and push-out strength (Ozeki et al 2001); facilitate bridging of small gaps between implants and surrounding bones (Søballe et al 1991; Stephenson et al 1991), reduce metal ion release from the metallic substrates (Surmenev et al 2010; Ducheyne and Healy 1988; Sousa and Barbosa 1996; Ozeki et al 2003); slow down metal degradation and/or its corrosion (Metikoš-Huković et al 2003; Yang et al 2008; Cheng and Roscoe 2005); accelerate bone growth (Cook et al 1992; Wang et al 2009), remodeling (Pilliar et al 1991; Yoon et al 2009) and osteointegration rate (Bigi et al 2008; Lee et al 2011); induce osteoconductivity (Cao et al 2010b), improve the early bone (Yang et al 1996; Mohammadi et al 2003) and healing (Vercaigne et al 2000b) responses; and result in lack of formation of fibrous tissues (Figure 11) (Layrolle 2011; Dostálová et al 2001), as well as increase the clinical performance of orthopedic hip systems (see below). In addition, calcium orthophosphate coatings, films and layers might be used for incorporation of drugs and important biologically active compounds, such as peptides, hormones and growth factors (Siebers et al 2006).…”
Section: Reviewmentioning
confidence: 99%
“…Some studies have indicated that implants with a coarse surface might be preferable compared with mechanically polished smooth titanium implants16. Shalabi et al6 observed that BIC was correlated with implant surface coarseness.…”
Section: Discussionmentioning
confidence: 99%